Accumulate or Diversify Ecological Innovation Assets? The Effect of Ecological Innovation Asset Depth and Breadth on Firm Financial Performance - Louisa Gropengießer-Arlt; Nicolas~A. Zacharias (Business Strategy and the Environment, 2025)
This study investigates the role of innovation portfolio structures in the relationship of ecological innovation and firm financial performance. We draw on the resource-based view and the natural resource–based view to examine the effects of the depth and breadth of firms' ecological innovation assets (EIAs) while conceptually and empirically accounting for the substantial differences between two distinct firm financial performance dimensions. To test our conceptual framework, we rely on a panel data set based on 340 US firms listed in the S&P 500 index over a 10-year period. Fixed-effects regressions confirm that EIA depth and EIA breadth fundamentally differ in their effects on firm financial performance. Moreover, we find that the results vary considerably between accounting-based and value-based financial performance. Thereby, this study makes a significant contribution to the ongoing debate about the nexus of ecological innovation and firm financial performance.
Keywords: 330; asset breadth; asset depth; ecological innovation; firm financial performance; resource-based view; technological portfolio